Microstructural features of Aisi 430 Ferritic Stainless Steel (FSS) Weld Produced under varying process parameter - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Universiti Malaya, 2009)
the microstructural features of the weld section which are controlled by the energy input and heat transfer factors. The welding current, travel speed and the material property govern these parameters. However, the specific influence of range of heat input rates on the microstructural features of FSS weld is hardly reported. This paper reports the microstructural features of FSS welds produced under different heat input rates. It has been observed that, irrespective of the welding condition, the primary solidification structure changed from a predominantly ferritic structure to a matrix interspersed with increasing fraction of inter-dendritic martensite in the weld metal and grain boundary martensite in the HAZ. The grain morphologies alternates between columnar and equiaxed grains depending on the welding speed within a given current. However, welding speed of 3.5mm/s appears to generally lead to the production of equiaxed grains.